KAJIAN IMPLEMENTASI GOOD CORPORATE GOVERNANCE PADA PENGELOLA ORGANISASI ZAKAT DI DOMPET DHUAFA KALIMANATAN TENGAH - Yusuf, Akhmad; Halidah, Nor; Mufidah, Nur Laily; Khairun Nisa, Siti (Program Studi Manajemen Zakat dan Wakaf, 2023)
This research intends to examine how good corporate governance grounded in the values of accountability, responsibility, independence, and fairness is applied to zakat management companies. This approach utilizes questionnaires to gather data and is qualitatively descriptive in nature. The research findings indicate that the implementation of good corporate governance (GCG) at Dompet Dhuafa Institution is based on the principles of accountability, independence, responsibility, transparency, and justice. The majority of respondents answered